Patient race, ethnicity, and care in the emergency department: A scoping review. Issue 2 (March 2020) - Owens, Allison; Holroyd, Brian R.; McLane, Patrick
ABSTRACT: Objectives: Health disparities between racial and ethnic groups have been documented in Canada, the United States, and Australia. Despite evidence that differences in emergency department (ED) care based on patient race and ethnicity exist, there are no comprehensive literature reviews in this area. The objective of this review is to provide an overview of the literature on the impact of patient ethnicity and race on the processes of ED care. Methods: A scoping review was conducted to capture the broad nature of the literature. A database search was conducted in MEDLINE/PubMed, EMBASE, CINAHL Plus, Social Sciences Citation Index, SCOPUS, and JSTOR. Five journals and reference lists of included articles were hand searched. Inclusion and exclusion criteria were defined iteratively to ensure literature captured was relevant to our research question. Data were extracted using predetermined variables, and additional extraction variables were added as familiarity with the literature developed. Results: Searching yielded 1, 157 citations, reduced to 153 following removal of duplicates, and title and abstract screening. After full-text screening, 83 articles were included. Included articles report that, in EDs, patient race and ethnicity impact analgesia, triage scores, wait times, treatments, diagnostic procedure utilization, rates of patients leaving without being seen, and patient subjective experiences. Authors of included studies propose a variety of possible causes for these disparities. Conclusions: Further research on the existence of disparities in care within EDs is warranted to explore the causes behind observed disparities for particular health conditions and population groups in specific contexts.